KOMPETENSI KEPALA SEKOLAH ABAD 21: SEBUAH TINJAUAN TEORETIS - Rais Hidayat; Vicihayu Dyah M; Himmatul Ulya (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2019)
The purpose of this study was to determine the competencies that principals must have in the 21st Century. Writing this article uses the literature review method, is there a qualitative descriptive data analysis technique by looking for theoretical references relevant to the cases or problems found. Based on the results of the analysis, the conclusions that answer the problem of this research are (1) the principal is someone who is given the task of leading a school, (2) the intended leadership is the ability to influence organizationalresources to move to follow orders to achieve goals (4) effective principal'sleadership in terms of entrepreneurial leadership, exemplary, intelligent, anddemocratic, (4) the 21st century is the era of technological advances in the fields of information, communication, and transportation, (5) the characteristics the 21st century which are available access anytime, faster computing, and communication that can be done from anywhere and anywhere, (6) Competencies that principals must have to face the 21st century, namely dimensions of personality,managerial, entrepreneurial, supervision, and social competence.